Determining fracture resistance of structural adhesives in mode-I debonding using double cantilever beam test : Određivanje lomne žilavosti konstrukcijskih ljepila prilikom odljepljivanja u Modu-I pomoću testa dvostruke konzole - Hlača, Ivan (Array, 2019)
Double cantilever beam (DCB) test is the most commonly used test for determining the fracture resistance of structural adhesive joints in mode-I debonding. Test specimens are composed of two equal plates that are glued together, and then exposed to the opening load causing crack propagation along the bonded surface. During the experiment, loadline displacement, applied force and crack length are measured continuously. Using these data, the fracture toughness of the adhesive can be computed by the procedure given in the relevant ISO standard (BS ISO 25217:2009). The calculations are based on simple beam theory and linear elastic fracture mechanics (LEFM) equations. In this paper, we will present the standard method for performing a DCB test and the method for data processing required to obtain the adhesive fracture toughness, i.e. the critical energy release rate. Experiments are performed for SikaPower® 4720 adhesive, applied with controlled thickness between the aluminium plates (adherends). After the curing period recommended by the adhesive manufacturer, DCB specimens with piano hinges are loaded by a tensile-testing machine. Loading is applied in the displacement-control mode because when the crack starts to propagate, the applied load drops. Using the optical measurement system GOM Aramis, complete displacement field is recorded during the experiment. Displacement field is then used to obtain the actual load-line displacement of the adherends (different than the one recorded on the tensile-testing machine grips) and the position of the crack tip. After syncing the measurements from different devices, fracture toughness for the adhesive is determined and a statistical analysis performed.